Integrasi Filsafat Pendidikan Islam dan Literasi Digital dalam Penguatan Karakter Generasi Muslim - Azizah Intan Nuraeni; Muhammad Syaifin Nuha; Yulia Rakhmawati (CV. ITTC INDONESIA, 2026)
The integration of Islamic educational philosophy and digital literacy is essential in responding to the moral challenges faced by Muslim generations in the digital era, marked by ethical decline, limited self-regulation, and the rapid expansion of information. This study aims to examine the role of Islamic educational philosophy in strengthening character through a digital literacy approach. The research employs a literature review method using philosophical, epistemological, and axiological perspectives based on various scholarly sources. The findings reveal that combining the values of tawhid, morality, and adab with digital literacy skills can foster a critical, prudent, and well-grounded Muslim generation. Furthermore, this integration enhances ethical awareness in technology use and supports the internalization of Islamic values in everyday digital practices.